SOCIAL WORK: A SOCIAL PARTNER IN ECONOMIC DEVELOPMENT - Lombard, Antoinette (Social Work/Maatskaplike Werk, 2008)
Like many other countries worldwide, South Africa has accepted the challenge to achieve the aim of the United Nations to alleviate poverty by half by the year 2015. Thin (2002:17) states that poverty is a clear indicator that an economic system is not working as well as it should. This view of poverty sees it as both a social issue and an economic phenomenon (Thin, 2002:23). The expression of poverty in both social and economic contexts is reflected in the “two worlds” character of the South African economy, which Terreblanche (in Lombard, 2008:23) describes as follows: